Drug delivery systems for treatment of temporomandibular joint osteoarthritis - Huang, Xinqi; Pan, Xuefeng; Xiong, Xiner; Zhao, Zhihe; Cen, Xiao (Frontiers in Pharmacology, 2022)
The number of people suffering from temporomandibular joint osteoarthritis (TMJOA) has been increasing. TMJOA cause joint noise, pain on TMJ and/or masticatory muscles, and restricted mandibular movement, which disturb eating, laughing and conversation, and impose serious lifestyle impediments. Chondrocyte apoptosis, extracellular matrix degradation, synovitis, and subchondral bone remodeling are the main pathological features of TMJOA. Various drug delivery systems are developed to controlled release at specific activation sites with high bioactivity and inhibit rapid dilution to enable long-term therapeutic response, which present great potential for the treatment of TMJOA. This review focuses on recently developed drug delivery systems by different administration in the TMJOA treatment, and summarizes their effects, duration, safety, and limitations, which would pave the way for development of TMJOA therapy.